2023
DOI: 10.1177/19485506231156061
|View full text |Cite
|
Sign up to set email alerts
|

Lonely Today, Lonely Tomorrow: Temporal Dynamics of Loneliness in Everyday Life and its Associations With Psychopathological Symptoms

Abstract: Although theory emphasizes that loneliness fluctuates in everyday life, most previous studies focused on the general and stable tendency of feeling lonely. In the present study, we used daily diary data collected over two 4-week periods ( N1 = 3,309; N2 = 907) to examine different indicators of temporal dynamics of loneliness in everyday life and compare them with temporal dynamics of positive and negative affect. Moreover, we examined associations between temporal dynamics of loneliness and psychopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Consistent with the extant literature (e.g., Buecker et al, 2024;Jessen et al, 2018;Svensson et al, 2022), people with higher average daily loneliness reported greater and more severe physical health symptoms. Past work examining individual differences in loneliness and physical health symptomology has typically relied on single assessments of trait loneliness (e.g., Svensson et al, 2022).…”
Section: Average Daily Lonelinesssupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with the extant literature (e.g., Buecker et al, 2024;Jessen et al, 2018;Svensson et al, 2022), people with higher average daily loneliness reported greater and more severe physical health symptoms. Past work examining individual differences in loneliness and physical health symptomology has typically relied on single assessments of trait loneliness (e.g., Svensson et al, 2022).…”
Section: Average Daily Lonelinesssupporting
confidence: 81%
“…To understand developmental or long-term stability (or change), then, researchers must consider short-term dynamics characterizing the phenomena. Pertinent to the current study, although loneliness has been considered a stable trait in research, it fluctuates across time (e.g., Buecker et al, 2024; Zhaoyang et al, 2022). Thus, understanding how loneliness functions in different time scales is a crucial factor to consider in relation to physical health symptoms.…”
Section: Loneliness and Health During Midlifementioning
confidence: 99%
See 3 more Smart Citations